Measurement of the 2D emission profiles of hydrogen and impurity ions in the TCV divertor. (March 2021) - Perek, A.; Linehan, B.L.; Wensing, M.; Verhaegh, K.; Classen, I.G.J.; Duval, B.P.; Février, O.; Reimerdes, H.; Theiler, C.; Wijkamp, T.A.; de Baar, M.R.; et al.
Abstract: Plasma emission of hydrogen and impurities is measured with use of filtered camera imaging in TCV divertor. The measurement technique is discussed in detail including: selection choice of filters, the absolute calibration procedure and the tomographic inversion. The process is applied to an unseeded L-mode density ramp discharge in an unfavorable for H-mode access magnetic field direction with divertor baffles. Obtained poloidal emission profiles are used to split Balmer emission into excitation and recombination parts revealing a recombination emission maximum on the high field side. The optical emission is further studied by selecting radial profiles in cross sections of interest finding an opposite radial shift direction for high and low n Balmer line emission maxima in detached conditions.